2014
DOI: 10.1371/journal.pone.0089382
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Alpha Suppression in Response to Facial Motion

Abstract: While biological motion refers to both face and body movements, little is known about the visual perception of facial motion. We therefore examined alpha wave suppression as a reduction in power is thought to reflect visual activity, in addition to attentional reorienting and memory processes. Nineteen neurologically healthy adults were tested on their ability to discriminate between successive facial motion captures. These animations exhibited both rigid and non-rigid facial motion, as well as speech expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 90 publications
2
7
1
Order By: Relevance
“…This was generally related to the desynchronization of mirror neurons activity as studied with EEG and fMRI combination (Arnstein et al, 2011 ), and would reflect a release from inhibition. However, it is interesting to note that our results are in contrast to studies of face perception (Girges et al, 2014 ), which report a greater alpha ERD in response to upright facial motion than in inverted condition. This difference between face and body motion recognition may be explain by high specialization of the brain to face recognition, and in particular to treatment of semantic content of facial gesture (Rojas et al, 2011 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was generally related to the desynchronization of mirror neurons activity as studied with EEG and fMRI combination (Arnstein et al, 2011 ), and would reflect a release from inhibition. However, it is interesting to note that our results are in contrast to studies of face perception (Girges et al, 2014 ), which report a greater alpha ERD in response to upright facial motion than in inverted condition. This difference between face and body motion recognition may be explain by high specialization of the brain to face recognition, and in particular to treatment of semantic content of facial gesture (Rojas et al, 2011 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The first alpha ERS is in accordance with recent studies showing similar transient alpha increase in response to upright facial motion (Girges et al, 2014 ). The suppression of the early alpha ERS in Upside-down suggest that the inversion of the body presentation rapidly affect the early visual process.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Girges et al . reported that an increase in alpha ERD at the parieto-occipital regions reflected activity of the face-specific posterior STS for higher attentional efforts allocated to perceiving upright facial motion [ 32 ]. Consistent with these findings, our results also demonstrated that alpha power for the preferred face group was more decreased than for the non-preferred face group, because the preferred faces required more intensive information processing that was likely to be reflected by alpha ERD.…”
Section: Discussionmentioning
confidence: 99%
“…The technique also allowed the authors to separate rigid and nonrigid motion, thus evaluating their contributions to the categorization of identity and gender, respectively. These stimuli have since been successfully implemented in other studies examining the discrimination of individual faces (O'Brien, Spencer, Girges, Johnston, & Hill, 2014;Spencer, O'Brien, Johnston, & Hill, 2006), viewpoint dependence (Watson, Johnston, Hill, & Troje, 2005), and neural correlates of facial motion perception within the visual cortex (Girges, Wright, Spencer, & O'Brien, 2014).…”
mentioning
confidence: 99%